Development and validation of prognostic dynamic nomograms for hepatitis B Virus-related hepatocellular carcinoma with microvascular invasion after curative resection - Bai, Shilei; Yang, Pinghua; Wei, Yanping; Wang, Jie; Lu, Caixia; Xia, Yong; Si, Anfeng; Zhang, Baohua; Shen, Feng; Tan, Yexiong; Wang, Kui (Frontiers in Oncology, 2023)
Background and Aim: The prediction models of postoperative survival for hepatitis B virus-related hepatocellular carcinoma (HBV-HCC) with microvascular invasion (MVI) have not been well established. The study objective was the development of nomograms to predict disease recurrence and overall survival (OS) in these patients. Methods: Data were obtained from 795 HBV-related MVI-positive HCC patients who had undergone curative resection from January 2014 to December 2017. The study was approved by the Eastern Hepatobiliary Surgery Hospital ethics committee, and patients provided informed consent for the use of their data. Nomograms for recurrence and OS were created by Cox regression in the training cohort (n=530) and were verified in the validation cohort (n=265). Results: The nomograms of recurrence and OS based on preoperative serological indicators (HBV-DNA, neutrophil-lymphocyte ratio, a-fetoprotein), tumor clinicopathologic features (diameter, number), surgical margin and postoperative adjuvant TACE achieved high C-indexes of 0.722 (95% confidence interval [ CI], 0.711-0.732) and 0.759 (95% CI, 0.747-0.771) in the training cohort, respectively, which were significantly higher than conventional HCC staging systems (BCLC, CNLC) .The nomograms were validated in the validation cohort (0.747 for recurrence, 0.758 for OS) had well-fitted calibration curves. Our nomograms accurately stratified patients with HBV-HCC with MVI into low-, intermediate- and high-risk groups of postsurgical recurrence and mortality. Prediction models for recurrence-free survival (https://baishileiehbh.shinyapps.io/HBV-MVI-HCC-RFS/) and OS (https://baishileiehbh.shinyapps.io/HBV-MVI-HCC-OS/) were constructed. Conclusions: The two nomograms showed good predictive performance and accurately distinguished different recurrence risks and survival rates by the nomograms scores for HBV-HCC patients with MVI after resection.